2015
DOI: 10.1371/journal.pone.0131558
|View full text |Cite
|
Sign up to set email alerts
|

PPI versus Histamine H2 Receptor Antagonists for Prevention of Upper Gastrointestinal Injury Associated with Low-Dose Aspirin: Systematic Review and Meta-analysis

Abstract: This study compared proton pump inhibitors (PPIs) and histamine H2 receptor antagonists (H2RAs) for prevention of low-dose aspirin (LDA)-related gastrointestinal (GI) erosion, ulcer and bleeding. Electronic databases including PubMed, Embase, Cochrane Central Register of Controlled Trials, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, and WanFang Data were searched from the date of their establishment to December 31, 2013. Randomized controlled trials comparing PPIs and H2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 45 publications
1
28
1
3
Order By: Relevance
“…They are more effective at lowering the risk of upper GI peptic ulcer bleeding than H2RAs (32). In the present study, PPIs significantly lowered the risk of peptic ulcer bleeding.…”
Section: Discussionsupporting
confidence: 53%
“…They are more effective at lowering the risk of upper GI peptic ulcer bleeding than H2RAs (32). In the present study, PPIs significantly lowered the risk of peptic ulcer bleeding.…”
Section: Discussionsupporting
confidence: 53%
“…Unfortunately, these strategies have not been studied head‐to‐head and there is no clearly superior strategy based upon available data. Furthermore, certain de‐escalation strategies may not be appropriate for all patients, as H2 blockers are inferior in reflux treatment and relapse regardless of GERD phenotype and do not prevent aspirin, NSAID, antiplatelet, or anticoagulant associated ulceration and bleeding . Our study found that physicians were not only changing their PPI prescribing habits, but also screening their patients on PPIs for bone disease more frequently.…”
Section: Discussionmentioning
confidence: 82%
“…Six articles fulfilled all criteria [28][29][30][31][32][33]. One systematic review [34] checked during the assessment cited six additional Chinese papers fulfilling inclusion criteria and showed data suitable for comparison. The committee of reviewers accepted the inclusion of data derived from these Chinese written articles [35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…All these raised the question whether the less expensive H2RAs are suitable to prevent aspirin-induced GI bleeding. The only meta-analysis published so far [34] comparing H2RAs to PPI in the prevention of ASA-related GI harms examined exclusively RCT studies up till 2013. In the present study we extended the review to a wider field including data of appropriate observational studies and more recent findings of literature.…”
Section: Discussionmentioning
confidence: 99%